STRATEGY DEVELOPMENT RESOURCE MAN DIGITAL BASED IN IMPROVING EMPLOYEE PERFORMANCE IN THE GREAT HALL TESTING TELECOMMUNICATION DEVICES, MINISTRY COMMUNICATION AND INFORMATICS - Ningsih, Sari; Hakim, Azis (Faculty of Law, Universitas Pekalongan, 2024)
Problem principal in study This is a development strategy source Power man Deep Digital Based increase performance employee at the Testing Center Telecommunications Equipment , Ministry of Communication and Information Republic of Indonesia not yet walk in a way effective and efficient . Problem main in study This is what is the development strategy source Power man Deep Digital Based improve it performance employee at the Testing Center Ministry of Communication and Information Technology Telecommunication Equipment Republic of Indonesia not yet walk in a way effective and efficient. Research methods used researcher is studies case use approach qualitative. Research result find effective development strategies digital- based sources Power man in increase performance employee at the Testing Center Telecommunications Equipment, Ministry of Communication and Information Republic of Indonesia, namely with give attention factor productivity work, efficiency, damage, accidents, service, morale work, career, conceptual, leadership, factors remuneration and consumers supported by the findings study that is factor creativity and factors innovative so that performance employee at the Central Telecommunication Equipment Testing Center, Ministry of Communication and Information Republic of Indonesia can walk in a way effective and efficient.